Neurological follow-up of small-for-gestational age newborn infants: a study of risk factors related to prognosis at one year of age - José Luiz D. Gherpelli; Helvetia Ferreira; Helenice P.F. Costa (Arquivos de Neuro-Psiquiatria)
To examine the relative importance of some risk factors and neurological prognosis in the first year of life, 37 small-for-gestational age newborns were followed prospectively to 1 year of conceptional age. An abnormal neurological examination was found in 51.3% of the newborns and, at 12 months, 32.5% were still considered abnormal. Only 8.1% of the group had severe neurological sequelae at 1 year of corrected age. The developmental tests showed little changes during the first year, with abnormality rates varying from 16.1 to 25%. The following risk factors were analyzed concerning their relation to neurological and developmental abnormalities: high-risk pregnancy, maternal hypertension, social class, pre-term birth, neonatal asphyxia and weight and height less than 2.5 percentile at the age of 1 year. The statistical analysis showed a high correlation between subnormal weight gain and neurological (p=0.000l) and developmental (p=0.001) abnormalities at 1 year. None of the other risk factors were statistically related to neurological prognosis at 1 year.